Importance of prostate volume in the stratification of patients with intermediate‐risk prostate cancer. (17th March 2015) - Moschini, Marco; Gandaglia, Giorgio; Suardi, Nazareno; Fossati, Nicola; Cucchiara, Vito; Damiano, Rocco; Cantiello, Francesco; Shariat, Shahrokh F; Montorsi, Francesco; Briganti, Alberto
<x xml:space="preserve">Abstract</x> Objectives To evaluate the role of prostate volume assessed at final pathology in the risk of biochemical recurrence in patients with clinically localized prostate cancer treated with radical prostatectomy. Methods Overall, 5637 patients treated with radical prostatectomy between January 1993 and August 2013 were identified. Multivariable Cox regression analyses tested the association between prostate volume and biochemical recurrence in the overall population and after stratifying patients according to the D'Amico risk groups. Results Mean (median) prostate volume was 50.61 mL (46 mL). When patients were stratified according to D'Amico risk groups, mean (median) prostate volume was 51.7 mL (48 mL), 49.8 mL (45 mL) and 50.6 mL (46 mL) in low‐, intermediate‐, and high‐risk prostate cancer, respectively (P = 0.04). Overall, the 5‐year biochemical recurrence‐free survival rate was 87.9%. In multivariable Cox regression analyses, prostate volume was associated with a lower risk of biochemical recurrence (hazard ratio 0.99, 95% confidence interval 0.99–1.00), after accounting for disease characteristics. However, when patients were stratified according to D'Amico risk groups, prostate volume represented an independent predictor of biochemical recurrence only in individuals with intermediate‐risk disease (hazard ratio 0.99, 95% confidence interval 0.99–1.00). Conversely, prostate volume was not associated with the risk of experiencing biochemical recurrence in patients with low‐ and high‐risk disease. Conclusions Smaller prostates are associated with increased risk of biochemical recurrence after surgery only in men with intermediate‐risk disease. In this category, the preoperative assessment of prostate volume might be helpful in order to identify patients at higher risk of biochemical recurrence after surgery. Additionally, prostate volume might be used to individualize follow‐up schedules after radical prostatectomy.